Pseudo-Benign Paroxysmal Positional Vertigo: A Retrospective Study and Case Report - Yu, Jie; Yu, Qianru; Guan, Benling; Lu, Yu; Chen, Chengfang; Yu, Shudong (Frontiers in Neurology, 2020)
Pseudo-benign paroxysmal positional vertigo (pseudo-BPPV) is a specific type of vestibular migraine disguised as benign paroxysmal positional vertigo, which is characterized by recurrent different types of positional and atypical positional vertigo with migraine features. It is easy to be misdiagnosed with BPPV at the first visit, which means that the ideal therapeutic effects are not achieved. Twenty-five cases of pseudo-BPPV with frequent changing positional vertigo were retrospected and the following key features help to identify the disease: recurrent positional and atypical positional vertigo, migrainous accompanying symptoms or migraine history, mild or indistinctive headaches, with or without impaired vestibular function, ineffective for simply reposition. And we found that vertigo in pseudo-BPPV can be preferable controlled by valproic acid combined with canalith repositioning procedure.